Factors influencing the clinical ineffectiveness of antibiotics in non-responders - Velusamy, Sivakumar; Thangavelu, Saravanan; Thomas, Monica Sherin; Harinathan, Monisha (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Antibiotic ineffectiveness and clinical non-responsiveness remain significant challenges in healthcare. Non-responders-patients who fail to improve despite appropriate antibiotic therapy-pose a substantial clinical burden. Identifying factors influencing such outcomes is essential for improving treatment success. To investigate patient, hospital-related factors contributing to antibiotic ineffectiveness despite culture sensitivity. Method: A six-month ambispective observational study was conducted at PSG Hospitals, Coimbatore, India. A total of 480 inpatients were included into the study. Highly prescribed antibiotics-Cefoperazone+Sulbactam, Meropenem, Piperacillin Tazobactam, and Ceftriaxone-were analyzed. Factors such as age, gender, type of bacteria, prior antibiotic exposure, prior hospitalization, invasive procedures, and length of hospital stay were examined. Statistical analysis was performed using SPSS, with p values < 0.05 considered significant. Results: Among 480 patients equally divided across four antibiotic groups, age was significant in the Meropenem group (p=0.044) in contrast to the rest of the groups. Prior antibiotic exposure (OR range: 1.091–1.889; p<0.05) and longer hospital stay (OR range: 1.271–1.710; p<0.001) were significantly associated with non-response across all the four antibiotic groups. Klebsiella pneumoniae was significantly linked to non-response across all groups (OR range: 1.025–1.801; all p<0.01). Invasive procedures were significant for Cefoperazone–Sulbactam (OR=2.148, p=0.030) and Piperacillin–Tazobactam (OR=1.643, p=0.012). Conclusion: Prior antibiotic exposure, prolonged hospital stays, and the presence of Klebsiella pneumoniae were significantly associated with antibiotic non-responsiveness. This suggests a multifaceted approach addressing patient, microbial, and institutional factors might lessen disruptions to optimal clinical effectiveness.